2022
DOI: 10.3390/v14030503
|View full text |Cite
|
Sign up to set email alerts
|

Critical View on the Importance of Host Defense Strategies on Virus Distribution of Bee Viruses: What Can We Learn from SARS-CoV-2 Variants?

Abstract: Bees, both wild and domesticated ones, are hosts to a plethora of viruses, with most of them infecting a wide range of bee species and genera. Although viral discovery and research on bee viruses date back over 50 years, the last decade is marked by a surge of new studies, new virus discoveries, and reports on viral transmission in and between bee species. This steep increase in research on bee viruses was mainly initiated by the global reports on honeybee colony losses and the worldwide wild bee decline, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…This study found a positive correlation between time of first grooming and ABPV levels in HVG bees, suggesting a possible effect of the viral infection in the ability of the bees to perform self-grooming. In addition to the above, exploring viral dynamics taking into consideration effects of individual defense mechanisms should be explored, as proposed by Piot and Smagghe ( 70 ), but also the effects of behavioral immune responses as it could provide more information about the impact of viruses, vectored and not vectored by V. destructor (like BQCV and Apis rhabdovirus-2 ), on honey bee health. This results not only emphasize the possible impact of viral infections on behavioral immune responses, but also that breeding programs should use genomic assisted selection to avoid the interference of stressors in the performance evaluations, such as V. destructor parasitism and viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…This study found a positive correlation between time of first grooming and ABPV levels in HVG bees, suggesting a possible effect of the viral infection in the ability of the bees to perform self-grooming. In addition to the above, exploring viral dynamics taking into consideration effects of individual defense mechanisms should be explored, as proposed by Piot and Smagghe ( 70 ), but also the effects of behavioral immune responses as it could provide more information about the impact of viruses, vectored and not vectored by V. destructor (like BQCV and Apis rhabdovirus-2 ), on honey bee health. This results not only emphasize the possible impact of viral infections on behavioral immune responses, but also that breeding programs should use genomic assisted selection to avoid the interference of stressors in the performance evaluations, such as V. destructor parasitism and viral infections.…”
Section: Discussionmentioning
confidence: 99%